Лабораторный практикум по курсу "Информатика" учебное пособие - Савельева Е. В. Елена Васильевна; Егорова О. В. Ольга Викторовна; Павлов В. М. Вадим Михайлович; Байдали Т. А. Тамара Алексеевна (Томск, Изд-во ТПУ, 2014)
Заглавие с титульного экрана